Monday

April 21, 2014

April 21, 2014

Posted by **tawana** on Tuesday, December 5, 2006 at 9:02pm.

Combine the "a" tems and you can reduce this to _?_a + 3b.

You do the math.

- algebra 1 -
**Jennifer**, Tuesday, October 30, 2012 at 8:41pma + (3a-2a)-(4a-3b)

=

a + 3a - 2a -4a +3b

= -2a + 3b

**Related Questions**

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

algebra - Subtract (4a^3+3b^3)-(2a^3+4a^2b-_5ab^2+3b^3) is the answer 2a^3+4a^2b...

algebra - combine and reduce 6b/3a + b/a = answer 3b/a

Algebra 2345678!! - Solve the system of equations using the Addition method. 2a...

maths algebra - 3a-2(2a+4) 3a-2(2a + 4) you multiply the parenthesis by -2, ...

MATH Matrix Equation - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 ...

Math Matrix EQ - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 then 2a...

Algebra - Remove the parentheses from the following expression, and combine like...

algebra - How do you multipl (3a-2b)(4a+3b)??